Formulation of dragon fruit (Hylocereus polirhizus) and rambutan fruit (Nephleum lappaceum) in jelly candy - Baihaqi, Muhammad Imam; Sari, Desy Ambar; Ihromi, Syirril (UNIVERSITAS MUHAMMADIYAH MATARAM, 2023)
Jelly candy is a soft-textured confectionary processed with the addition of hydrocolloid components such as agar, gum, pectin, starch, carrageenan, gelatin, or others used to produce a chewy product. This study aims to determine the formulation of dragon fruit pulp and rambutan fruit on the chemical and organoleptic properties of jelly candy that the panelists like. The method used in this study was an experimental method using a completely randomized design (CRD) with two factors, namely the formulation of dragon fruit pulp and rambutan fruit in the manufacture of jelly candy which consisted of 5 treatments: T1 = 80% dragon fruit pulp + 20% fruit pulp rambutan, T2 = 70% dragon fruit pulp + 30% rambutan fruit pulp, T3 = 50% dragon fruit pulp + 50% rambutan fruit pulp, T4 = 30% dragon fruit pulp + 70% rambutan fruit pulp, T5 = 20% fruit pulp dragon + 80% rambutan pulp. The research data were analyzed using the Analysis of Variance of Diversity Analysis at the 5% significance level. Further tests were carried out with the Honest Significant Difference test at the 5% level. In conclusion, the best treatment was T2 (70% dragon fruit pulp + 30% rambutan pulp) with a moisture content of 44.515%, ash content of 0.385%, antioxidant content of 3.61%, reducing sugar content of 3.24%, aroma value score of 4, 13 with liking criteria, a color score of 4.13 with liking criteria, a very purplish red score, a texture score of 4.20 with supple criteria, and a taste score of 3.27 with rather like criteria.